2008
DOI: 10.1111/j.1539-6053.2009.01038.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning Styles

Abstract: The term "learning styles" refers to the concept that individuals differ in regard to what mode of instruction or study is most effective for them. Proponents of learning-style assessment contend that optimal instruction requires diagnosing individuals' learning style and tailoring instruction accordingly. Assessments of learning style typically ask people to evaluate what sort of information presentation they prefer (e.g., words versus pictures versus speech) and/or what kind of mental activity they find most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
405
2
10

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,386 publications
(541 citation statements)
references
References 39 publications
(63 reference statements)
16
405
2
10
Order By: Relevance
“…This is consistent with the idea that what really facilitates learners' success is not whether their learning styles match or mismatch a specific teaching programme or strategy, or the teacher's cognitive characteristics, but the very process whereby personal learning styles are reckoned and taken into account (e.g. Coffield et al 2004;Constantinidou and Baker 2002;Evans and Waring 2009;Glenn 2009;Massa and Mayer 2006;Pashler et al 2009). Our results also confirm that, as is assumed in the paradigm of self-directed learning (Brookfield 2009), the more the learners are allowed to participate responsibly, the better their attitude is toward the construction of knowledge.…”
Section: The Relation Between the Educators And The Learnerssupporting
confidence: 59%
“…This is consistent with the idea that what really facilitates learners' success is not whether their learning styles match or mismatch a specific teaching programme or strategy, or the teacher's cognitive characteristics, but the very process whereby personal learning styles are reckoned and taken into account (e.g. Coffield et al 2004;Constantinidou and Baker 2002;Evans and Waring 2009;Glenn 2009;Massa and Mayer 2006;Pashler et al 2009). Our results also confirm that, as is assumed in the paradigm of self-directed learning (Brookfield 2009), the more the learners are allowed to participate responsibly, the better their attitude is toward the construction of knowledge.…”
Section: The Relation Between the Educators And The Learnerssupporting
confidence: 59%
“…Matching the learning environment to people's cognitive style (‘matching hypothesis’; cf. Kolb, 1986; Kozhevnikov, Evans, & Kosslyn, 2014; but also Pashler et al, 2008, for an opposite view) might thus enhance learning effects, even though matching material to the specific context seems to be more important and would likely override any cognitive style matching effects (Klein, 2003; Kolloffel, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…A verbal cognitive style is still part of this model. The authors have found some promising results regarding reliability and validity of these three scales, which might lead the way towards the ‘hard evidence’ for the significance of this individual difference demanded by Pashler et al (2008). …”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Many studies have appeared both supporting and criticizing learning styles theories and instruments, including a body of research critical of learning styles that begins largely with Curry (1990) and extends to Pashler et al (2008), who conducted a review of the literature and found an inadequate evidence base to justify incorporating learning styles into educational practice. A number of studies have explored learning styles as applied to library instruction.…”
Section: Commentarymentioning
confidence: 99%